The Effect of Quality of Service And Price on Consumer Purchase Interest in Two Cipete Coffee In The City of Jakarta Selatan - Gojali Supiandi; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
The purpose of this study was to determine the effect of service quality and price on consumer buying interest at Dua Coffee Cipete in South Jakarta City. The method used is quantitative associative. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. From the results of research, service quality has a significant effect on consumer buying interest with the regression equation Y = -0.351 + 0.768X1, the correlation value of 0.762 means that the two variables have a strong level of relationship. The value of the coefficient of determination is 58.0%. Hypothesis test obtained t count > t table or (2,567 > 1,984). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant effect of service quality on consumer buying interest. Price has a significant effect on consumer buying interest with the regression equation Y=1.814 + 1.209X2, the correlation value of 0.805 means that the two variables have a strong relationship level. The value of the coefficient of determination is 64.7%. Hypothesis test obtained t count > t table or (5,138 > 1,984). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant effect of price on consumer buying interest. Service quality and price simultaneously have a significant effect on consumer buying interest with the regression equation Y = - 1.157 + 0.285X1 + 0.849X2. The correlation value of 0.818 means that the independent variable and the dependent variable have a very strong relationship level. The value of the coefficient of determination is 67.0%. Testing the hypothesis obtained the value of F arithmetic > F table or (98.366 > 2.700). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant effect of service quality and price on consumer buying interest.